Analisis Dampak Tingkat Pendidikan Ibu dan Pemberian Asi Eksklusif terhadap Prevalensi Stunting pada Anak Balita di Palangkaraya - Amalia Octavianny; Bahtiyar Mandala Sutra (Jurnal Syntax Admiration, 2025)
Stunting is one of the serious health problems in Indonesia, especially in children under five. This study aims to analyze the impact of maternal education level and exclusive breastfeeding on the prevalence of stunting in Palangka Raya. The research method used in this study uses quantitative methods and cross-sectional approaches with univariate data analysis and bivariate analysis. The univariate analysis aims to describe the distribution of toddlers based on age, gender, maternal education level, distribution of exclusive breastfeeding, and nutritional status of toddlers based on health profile data in the form of a frequency distribution table. This study involved 540 respondents consisting of mothers and children under five. The results of the study showed that there was a significant relationship between the level of maternal education and exclusive breastfeeding and the incidence of stunting in toddlers in Palangka Raya.